PERKEMBANGAN EKSPOR KOPI INDONESIA DI MASA PANDEMI COVID-19 - Kusuma Arden, Ida Bagus Wibisana; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to determine the effect of COVID-19, coffee prices, and exchange rates simultaneously and partially on Indonesian coffee exports. The research was conducted in Indonesia in the monthly time period from 2018-2020 so that the number of observations was 36 observations. The research data was obtained through the government's official website as well as articles related to research which were then analyzed using multiple linear regression analysis techniques. Based on the results of the study, it was found that simultaneously COVID-19, coffee prices, and the exchange rate had a significant effect on Indonesian coffee exports. Partially, the COVID-19pandemic variable has a negative effect, while the exchange rate variable has a positive effect on Indonesian coffee exports. The price variable has no significant effect on Indonesian coffee exports. This result has the implication that the pandemic causes a decrease in the value of coffee exports compared to when there was no pandemic. This is because the pandemic will affect the economy of Indonesian coffee importing countries so that it will reduce Indonesian coffee exports.